An underestimated factor: the extent of cross-reactions modifying APIs in surface-modified liposomal preparations caused by comprised activated lipids - Sauter, Max; Burhenne, Jürgen; Haefeli, Walter E.; Uhl, Philipp (Molecules, 2020)
Despite the nowadays available plentitude of strategies to selectively introduce functional surface modification of liposomes, in preclinical research this process is still primarily performed after liposomal preparation utilizing comprised activated phospholipids with functionalized head groups. However, because these activated lipids are present during the liposomal preparation process, they can cross-react with incorporated drugs, especially the particularly often utilized active esters and maleimide groups. Macromolecular drugs, being composed of amino acids, are particularly prone to such cross-reactions due to their often multiple reactive functionalities such as amino and disulfide groups. To demonstrate this impact on the formulation in liposomal surface modification, we assessed the extent of cross-reaction during the liposomal preparation of two activated phospholipids with typically used head group functionalized phospholipids, with the two peptide drugs vancomycin and insulin comprising disulfide and amino functionalities. Both drugs revealed a considerable fraction of covalent modification (estimated 2 to 12%) generated during the liposome preparation process with comprised activated lipids. Modification of the active pharmaceutical ingredients (APIs) was determined by high-resolution mass spectrometric analysis. These findings clearly demonstrate the non-negligibility of potential cross reactions using the post preparation liposomal surface modification strategy in preclinical research.
Gesehen am 04.01.2021